The anlysis on versions and spreading of Three Character Clssic on christianty in Chinese - QIAO, Yangmin (Journal of Research for Christianity in China (JRCC), 2025)
The missionaries in modern China draw on the experience of the elementary book of ancient China.By linking religious tract with Chinese native culture,they created various Three Character on Chriatianity.It uses the format of three words for one sentence to spread christianity,among which the three character classic written by Medhust, the revised edition,annotated edition of it and other kinds of christian three character classic including those written by Chinese Christian were widely spread.This article tries to carding and anlysis the version and the course of spread of three character classic on christianity, then excavating the question of chinization on the Chinese-western culture exchange of the publishing three character classic on christinity to providesome materials to the research of the reglious tract on chriatianity in chinese.